Characterization of a phenotypically severe animal model for human AB-Variant GM2 gangliosidosis - Deschenes, Natalie M.; Cheng, Camilyn; Khanal, Prem; Quinville, Brianna M.; Ryckman, Alex E.; Mitchell, Melissa; Pshezhetsky, Alexey V.; Walia, Jagdeep S. (Frontiers in Molecular Neuroscience, 2023)
AB-Variant GM2 gangliosidosis (ABGM2) is a rare and lethal genetic disorder caused by mutations in the GM2A gene that lead to fatal accumulation of GM2 gangliosides (GM2) in neurons of the central nervous system (CNS). GM2A encodes a transport protein known as GM2 activator (GM2A) protein, which is essential for degrading GM2 into their GM3 form. ABGM2 presents in infantile-, juvenile-, and adult-onset forms; of the three, the infantile-onset is the most prominent, and by far the most severe, as evidenced by high levels of GM2 accumulation, widespread neurodegeneration, and death by the age of 4. Gm2a−/− mice are commonly used as a model of ABGM2. These mice are characterized by phenotypes most representative of predicted adult-onset form of ABGM2, which include moderate GM2 accumulation and mild neurological defects. This mild phenotype has been attributed to compensation by alternative GM2 degradation pathways mediated by sialidase, neuraminidase 3 (NEU3), a pathway that is more prominent in mice than humans. To assess the extent to which NEU3 contributes to GM2 degradation, we generated double knock-out (Gm2a−/−Neu3−/−) mice. Compellingly, these mice present with a clinical phenotype resembling that of a more severe ABGM2, including ataxia, reduced mobility and coordination, weight loss, poor body scores, and lethality by 6–7 months. Furthermore, these phenotypes correlate with a dramatic increase in GM2 accumulation in the CNS compared to levels observed in either Gm2a−/− or Neu3−/− mice. Taken together, these studies, for the first-time, confirm that the mild neurological phenotype of Gm2a−/− mice is due to compensatory activity on GM2 catabolism through an alternate breakdown pathway involving NEU3. These studies support the use of double knockout mice as a novel and highly relevant model for pre-clinical drug studies in a more severe form of ABGM2.